Emerging drugs for primary Sjögren's syndrome. (3rd April 2019) - Gandolfo, Saviana; De Vita, Salvatore
ABSTRACT: Introduction : Primary Sjögren's syndrome (pSS) is an autoimmune systemic disease characterized by a complex and not yet completely elucidated etiopathogenesis, where autoimmune manifestations coexist with different degree of lymphoproliferation, resulting in multiple possible scenarios extremely heterogeneous from patient to patient. Although considerable progress has been made in the identifications of potential novel therapeutic targets in recent years, the biological complexity of pSS, combined to such heterogeneous clinical manifestations, makes the treatment of pSS, even today, a great challenge. Areas covered : A therapy specifically approved for pSS is still lacking. In recent years, several novel promising agents are being tested in pSS. Based on a deep revision of drugs evaluated for pSS therapy, it is striking that several clinical trials, some of them testing very promising agents, failed. Expert opinion : a renewal of clinical trial design, including the definition of novel inclusion criteria and outcome measures, together with the development of a stratification model of pSS patients and the advance in the definition of pathogenetic mechanisms underlying peculiar pSS subsets, represent preliminary and crucial steps to overcome the current therapeutic impasse in pSS.